Mapping coordination within a competitive dialogue process : Studying the setting of sustainability goals and their fulfillment in municipality urban development - Törnå, Niklas (Luleå tekniska universitet, Industriellt och hållbart byggande, 2022)
Several of Sweden’s municipalities have coordinated some of their urban development in dialogues processes to increase the fulfillment of stated sustainability goals (SGs). This thesis aims to increase the knowledge of how coordination occurs within a Competitive Dialogue Process (CDP) between and within the municipality and the building actors. To translate from the series of activities present in the municipalities building process to how the municipality coordinate towards fulfilling stated sustainability goals, I have used my understanding of Henry Mintzberg’s (1979) coordination mechanisms (CMs): Direct supervision, Mutual adjustment, Standardization of skills & norms, work, and outcome. The CMs are directly connected to if coordination occurs in an organization (means of coordination), while other concepts such as decentralization/centralization (Mintzberg, 1979; Thompson, 1967;March & Simon, 1958; et al.) are not directly connected to coordination (conditions for coordination). Decentralization/centralization within an organization can create coordination, but it is not certain since an organization could, for example, be decentralized and have no coordination. With the coordination mechanisms and the concepts of means of coordination/conditions for coordination, I have conducted a deductive case study with interviews and workshops with Luleå kommun, five other comparison municipalities, and selected building actors present in Luleå kommuns CDP “Nature town”. The major findings from the thesis are: - A mapping of a series of activities in the CDP, where two stages occurred: The criteria formulation and the follow-up/checking. - When the CMs are applied to the activities within the CDP, a trend emerged where standardization was more visible at the criteria formulation stage. Since CMs are means of coordination, the lack of standardization in the later stage of the CDP could impact the fulfillment of stated SGs. - A vertical dimension was introduced where the activities were categorized as either ...